Privatization Through Building Use Rights in The Tangerang Sea Fence Area According to Positive Law - Asyidqi, Alfi Taufiq; Dwiyanto, Sultan Alvaro; Amrullah, Anwar Hafidz (Fakultas Hukum, Universitas Islam Bandung, 2024)
The privatization of marine space in Tangerang through sea fences and Building Use Rights (HGB) certificates harms the local economy. All forms of natural resource privatization in Indonesia must consider their legality. The purpose of this research is to analyze the legality of the Tangerang Sea fence and the legal certainty of HGB certificates in the privatization of marine space. This research uses a normative juridical approach with secondary data. The research results indicate that this privatization violates Indonesian positive law because it does not meet the licensing procedures, contradicts Article 33, paragraph 4 of the 1945 Constitution, and harms the community. The HGB certificate is also invalid because it violates spatial planning regulations and the principle of common property.